"Be Careful, Cowboy": The Translation and Mutation of the Western Genre in Red Hill. Issue 5 (3rd September 2017) - Moll, Nicholas
Abstract: The western genre has long been hailed as an iconic expression of the United States' history and culture. However, the 2010 Australian film Red Hill (dir. Patrick Hughes, 2010) actively engages the genre's tropes, styles, and conventions. In doing so, the film converts the ideas of a ruggedly individualistic frontier, key to the western genre and the popularised notions of nineteenth-century United States expansion, to the contemporary Australian context, providing a translation and mutation of the western genre. This paper argues that, through disassociation of the western genre from the United States, Red Hill's frontier is made Australian over the course of the film, exploring the lingering traumas and ongoing violence of a specific colonisation process. Drawing on theories of genre, history, and postcolonialism, this paper investigates the exploration of national character, history, and boundaries through the western genre. In doing so, this paper situates the western genre as having a nationalistic function in general, rather than one associated with any particular nation, and as providing a touchstone for ideas of history and themes of colonial expansion in a contentious landscape of class, race, and society.